Short-Term Modifications of Postural Balance Control in Young Healthy Subjects After Moderate Aquatic and Land Treadmill Running - Rizzato, Alex; Bosco, Gerardo; Benazzato, Michael; Paoli, Antonio; Zorzetto, Giulia; Carraro, Attilio; Marcolin, Giuseppe (Frontiers in Physiology, 2018)
Postural balance control can be altered by land treadmill (LTM) running. This impairment seems to be related to a disturbance of vestibular and visual information. However, no studies are available on aquatic treadmill (ATM) running. The aim of the present study was to investigate the effect of running at moderate intensity over ATM and LTM on the postural balance control both with opened (OE) and closed (CE) eyes. Center of pressure trajectory of 20 healthy subjects was collected on a dynamometric platform before and after a 20-minute-long running on ATM and LTM at the same rate of perceived exertion (Borg’s scale: 3/10). Heart rate (HR) was recorded every 30 s during running. Stabilogram diffusion analysis (SDA) and sample entropy (SampEn) were calculated to deepen motor control mechanisms. HR values were lower during ATM running with respect to LTM running (p < 0.01). A significant effect of the treadmill factor was detected in the OE condition for the sway path (p<0.01; p2 = 0.364; Power: 0.879), the sway area (p<0.01; p2 = 0.324; Power: 0.816) and the ML oscillations (p<0.01; p2 = 0.390; Power: 0.911) while an effect of the time factor was detected for the ellipse area (p<0.05; p2 = 0.213; Power: 0.576). However, the effect size for all the parameters ranged from 0.06 (trivial) to 0.48 (small). In the OE condition, the SDA highlighted a significant effect of the treadmill factor on all the short-term diffusion coefficients which negatively influenced the open loop motor control strategies. In the CE condition, SampEn analysis underlined a significant decrease of the center of pressure regularity after LTM running. Although slight modifications of the mechanisms involved in the postural balance control occurred, ATM and LTM moderate running did not seriously threaten postural balance performance. Therefore, the usage of ATM should be taken into account in all those situations where the well-known advantages of the aquatic environment are priorities.